Merger in contests - Steffen Huck; Kai A. Konrad; Wieland Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Competition in some markets is a contest. This paper studies the merger incentives in such markets. Merger can be profitable. The profitability depends on the post-merger contest structure, the discriminatory power of the contest and on the number of contestants.
urn:nbn:de:kobv:11-10047063
Keywords: D44; L11; L13; 330; contests; merger